Study of Spectroscopic Properties of Pure and Nd Doped Ca3La2(BO3)4 Glasses. (2016) - Harde, Gajanan B.; Muley, Gajanan G.
Abstract: In this paper, we report pure and 5 mol% Nd doped Ca3 La2 (BO3 )4 glasses and their spectroscopic properties. A ternary system La2 O-3CaO-4H3 BO3 was adopted and glasses were prepared by using a conventional melt quenching technique. The amorphous nature of the glasses has been confirmed by powder X-ray diffraction analysis. In order to study the spectroscopic properties of fabricated glasses, ultraviolet-visible transmission and absorption spectroscopy has been performed. The absorption spectrum of Nd doped glass shows that the transition 4 I9/2 → 4 G5/2 + 2 G7/2 is more intense as compared to the other transitions. Optical band gap energies of both glasses have been determined and found decreased for Nd doped glass as compare to pure glass.